2022
DOI: 10.12998/wjcc.v10.i30.11074
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow metastatic neuroendocrine carcinoma with unknown primary site: A case report and review of the literature

Abstract: BACKGROUND Metastatic neuroendocrine carcinoma (NEC) of bone marrow is uncommon. Here, we report a case of bone marrow metastatic NEC with an unknown primary site. CASE SUMMARY A 73-year-old Chinese woman was admitted to our hospital because marked chest distress and asthma lasting 1 d on March 18, 2018. She was initially diagnosed with pulmonary infection, cardiac insufficiency, thrombocytopenia and severe anemia. Following treatment with antibiotic therapy, diuresis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Regarding the unknown primary tumor site in the case of neuroendocrine carcinoma, the authors suggested that the primary site might have regressed spontaneously or been unexplored due to a lack of sensitive imaging studies. 7 Our CUPS cases were possibly to be caused similarly. Alternatively, the primary site(s) may emerge in future thorough investigations if they survive longer.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Regarding the unknown primary tumor site in the case of neuroendocrine carcinoma, the authors suggested that the primary site might have regressed spontaneously or been unexplored due to a lack of sensitive imaging studies. 7 Our CUPS cases were possibly to be caused similarly. Alternatively, the primary site(s) may emerge in future thorough investigations if they survive longer.…”
Section: Discussionmentioning
confidence: 67%
“…5 Among DCBM/CUPS cases, adenocarcinoma, neuroendocrine carcinoma, and melanoma have been described. [6][7][8] Although the primary site can generally be suspected from the morphology and immunohistochemistry of metastatic cells in the bone marrow and can be identified by endoscopic and imaging (CT/ MRI/ FDG PET-CT) studies, there are still cases of CUPS, such as the case of melanoma, in which bone marrow biopsy detected HMB-45-and S100-positive atypical large cells with brown pigmentation; however, skin lesions were not observed on the body surface. 8 Over the past 6 years since 2017, we experienced 8 cases of DCBM, two of which were DCBM/CUPS cases.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow smear and bone marrow biopsy are the gold standard for the diagnosis of BMMs ( 9 ). However, it is not possible to identify tumour cells in a single bone marrow aspiration, since BMMs are multifocal and myelofibrosis occurs which increases the difficulty of obtaining the bone marrow ( 10 ). Multi-site bone marrow aspiration should be performed if necessary.…”
Section: Discussionmentioning
confidence: 99%